The role of playground games in the syntactic development in Sudanese children / Abubakr Abdalgadir Mohammed Abdalla - Mohammed Abdalla, Abubakr Abdalgadir (2012)
This study explores the playground games performed by Sudanese preschoolers and school going age children in an effort to determine the role of these in the syntactic development among its performers. The researcher’s own children as well as Sudanese students in some international schools in Kuala Lumpur form the population of participants in this study. The study adopts a qualitative research method and its data is collected by means of tape recording, transcribed and analyzed using the Minimalist Program which is latest development in Generative Grammar as a framework of analysis. This is done to determine foremost the grammaticality of sentences used in the games, secondly to discover the prevailing types of communicative syntactic units provided by the games for its performers and the developmental significance of these units. Analysis of data shows that grammatically correct “WH” questions and negative sentences are heavily used in the language of the games. These are found to be of particular significance for the syntactic development of the age group of games performers who are expected to acquire questions and negative sentences needed especially in conversations by this age (four and above). The playground games under study are found to play a positive role in syntactic development of its performers. These games act as a platform for children to practise the type of sentences detected in their verbal component.